Risk of Developing GDM Gestational Diabetes Mellitus in Singleton and Twin Gestation with Use of 17 Hydroxyprogesterone Caproate - Saleem, Hafiza Asifa; Ashraf, Viqar; Sajjad, Rabia; Zainab Ch, Sadia; Hayat, Naheed; Asif Rehman, Hafiz Muhammad (Indus Journal of Bioscience Research, 2025)
Background: The use of 17P to prevent preterm birth is well-documented, but its potential effect on the development of GDM is not well understood. Objective: This study was planned with object to deeply study the effect of 17P on the occurrence of GDM in pregnant women, comparing its effects to a placebo in both single and multiple pregnancies. Methodology: In this prospective short study, total 198 pregnant females were recruited. Study group 17P and placebo group formed thorough randomization and the gestation age was between 16 to 36 weeks. The primary outcome measured was the occurrence of GDM, diagnosed via the OGTT administered during the 24th to 28th weeks of pregnancy. Results: GDM was observed in 16.33% of the participants in the 17P group, while it was observed in 18% of those in the placebo group, with no statistically significant difference observed (p=0.755). Subgroup analyses considering factors such as type of pregnancy, obesity, and history of diabetes also showed similar non-significant outcomes. Conclusion: The findings indicate that 17-alpha Hydroxy Progesterone Caproate does not significantly affect the development of GDM in pregnant females. These results support the continued use of 17P in pregnancies at risk of premature birth without increasing the risk of GDM.